Fuzzy Based Controlling For Accurate Temperature In Poultry Machinary - Sigit Prakosa Adhi Nugraha; Arief Marwanto; Muhammad Qomaruddin (Universitas Islam Sultan Agung, 2018)
Generally, thermostat is used to control temperature manually. However, unstability temperature has rises during egg hatching proces operates. It’s coverage more than 38,2 0C and cannot automated controlled. Therefore, egg hatch temperature should be controlled to avoid the damage of eggs and sensor. To addresing this limitation, fuzzy logic based algorithm is proposed with arduino and DHT 11 are uses which controlled temperature is stabilizer. During experimentally setup, the result shows that using fuzzy logic and arduino is able to perform good controller of egg hatching machine. The productivity of egg becoming poultry is rises 92%. Experimental shows that, by wading 20 egg in hatching machine, the prototype device able to stabilized temperature in 15 minutes into 37-38,2 0C.